Effect of hyoscine butylbromide (Buscopan®) on cholinergic pathways in the human intestine. Issue 8 (19th May 2013) - Krueger, D.; Michel, K.; Allam, S.; Weiser, T.; Demir, I. E.; Ceyhan, G. O.; Zeller, F.; Schemann, M.
Abstract Background Hyoscine butylbromide (HBB, Buscopan®) is clinically used to treat intestinal cramps and visceral pain. Various studies, mainly on animal tissues, suggested that its antimuscarinic action is responsible for its spasmolytic effect. However, functional in vitro studies with human tissue have not been performed so far. Methods We wanted to provide a comprehensive study on the mode of action of HBB in human intestinal samples and investigated HBB (1 nmol L−1–10 μmol L−1) effects on muscle activity with isometric force transducers and calcium imaging, on epithelial secretion with Ussing chamber technique and on enteric neurons using fast neuroimaging. Key Results Hyoscine butylbromide concentration dependently reduced muscle contractions, calcium mobilization, and epithelial secretion induced by the muscarinic agonist bethanechol with IC50 values of 429, 121, and 224 nmol L−1, respectively. Forskolin‐induced secretion was not altered by HBB. Cholinergic muscarinic muscle and epithelial responses evoked by electrical nerve stimulation were inhibited by 1–10 μmol L−1 HBB. Moreover, HBB significantly reduced the bethanechol‐induced action potential discharge in enteric neurons. Interestingly, we observed that high concentrations of HBB (10 μmol L−1) moderately decreased nicotinic receptor‐mediated secretion, motility, and nerve activity. Conclusions & Inferences The results demonstrated the strong antimuscarinic action of HBB whereas the nicotinic antagonism at higher concentrations plays at most a moderate modulatory role. The muscle relaxing effect of HBB and its inhibition of muscarinic nerve activation likely explain its clinical use as an antispasmodic drug. Our results further highlight a so far unknown antisecretory action of HBB which warrants further clinical studies on its use in secretory disorders.